2019
DOI: 10.3332/ecancer.2019.967
|View full text |Cite
|
Sign up to set email alerts
|

Complete metastasectomy in renal cell carcinoma: a propensity-score matched by the International Metastatic RCC Database Consortium prognostic model

Abstract: Introduction: We evaluated overall survival (OS) benefit of complete metastasectomy (CM) in metastatic renal cell carcinoma (mRCC) using a propensity score-matched (PSM) analysis to balance groups by age, gender and by the International Metastatic RCC Database Consortium prognostic model (IMDC). Methods: We included patients (pts) treated at the AC Camargo Cancer Center between 2007 and 2016. Pairs were matched by age, gender and IMDC. Kaplan-Meier survival estimates and Cox proportional hazard models were use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Alt et al demonstrated that complete surgical resection of multiple RCC metastases was associated with a prolonged median cancer specific survival (CSS) to 4.8 years and, in fact, significantly improved the 5-year CSS rate (49.4%) compared with the rate among patients who did not undergo complete metastasectomy (13.9%) [ 17 ]. This benefit of metastatic resection has been confirmed by many other authors [ 18 20 ]. Therefore, wide resection with curative intent seems to be the primary approach to solitary or oligometastatic bone metastasis [ 13 ].…”
Section: Discussionsupporting
confidence: 68%
“…Alt et al demonstrated that complete surgical resection of multiple RCC metastases was associated with a prolonged median cancer specific survival (CSS) to 4.8 years and, in fact, significantly improved the 5-year CSS rate (49.4%) compared with the rate among patients who did not undergo complete metastasectomy (13.9%) [ 17 ]. This benefit of metastatic resection has been confirmed by many other authors [ 18 20 ]. Therefore, wide resection with curative intent seems to be the primary approach to solitary or oligometastatic bone metastasis [ 13 ].…”
Section: Discussionsupporting
confidence: 68%
“…Several studies demonstrated that certain patient populations had a lack of clinical improvement with metastasectomy for mRCC. Fares et al compared 37 MTX patients with 37 PSM non-MTX patients and found that the OS benefit of MTX was absent in patients with poor International Metastatic RCC Database Consortium (IMDC) risk stratification (33). Similarly, while Wu et al demonstrated a significant decrease in CSM overall, a sub-analysis revealed that only IMDC favorable-risk patients benefitted from MTX, whereas no significant difference was observed for intermediate and high-risk patients (24).…”
Section: Metastasectomy Status and Clinical Outcomesmentioning
confidence: 99%
“…Both models have been externally validated and are effective in predicting outcomes for mRCC patients (88)(89)(90)(91). Multiple studies that have already been discussed in this text have demonstrated beneficial outcomes for mRCC patients with favorable-risk grouping in the MSKCC and IMDC models who undergo MTX, while patients with poor-risk stratification may fail to benefit from MTX (33,68,79,81)…”
Section: Risk Stratificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Utilization of MTS is increasing, with rates increasing from 24.9% in 2006 to 31.4% in 2013 [11]. Since 2017 alone, eight retrospective studies have reexamined survival benefits of complete MTS (which surgically removes all gross metastases) in the treatment of mRCC, compared to incomplete or no-MTS [11][12][13][14][15][16][17][18][19] (Table 1). To evaluate the effect of complete MTS in the era of TT and ICI availability, Lyon et al assessed the likelihood of death from RCC in 403 patients.…”
Section: Complete Vs Incomplete Metastasectomymentioning
confidence: 99%